Diversification of Antitumour Immunity in a Patient with Metastatic Melanoma Treated with Ipilimumab and an IDO-Silenced Dendritic Cell Vaccine - Mouldy Sioud; Marta Nyakas; Stein Sæbøe-Larssen; Anne Mobergslien; Steinar Aamdal; Gunnar Kvalheim (Case Reports in Medicine)
Indoleamine 2,3-dioxygenase (IDO) expression in dendritic cells (DCs) inhibits T-cell activation and promotes T-cell differentiation into regulatory T-cells. Moreover, IDO expression promotes resistance to immunotherapies targeting immune checkpoints such as the cytotoxic T lymphocyte antigen-4 (CTLA-4). Here, a patient with metastatic melanoma pretreated with ipilimumab, an anti-CTLA-4 blocking antibody, was vaccinated with IDO-silenced DCs cotransfected with mRNA for survivin or hTERT tumour antigens. During vaccination, T-cell responses to survivin and hTERT tumour antigens were generated, and a certain degree of clinical benefit was achieved, with a significant reduction in lung, liver, and skin metastases, along with a better performance status. T-cell responses against MART-1 and NY-ESO-1 tumour antigens were also detected in the peripheral blood. The patient also mounted an antibody response to several melanoma proteins, indicating diversification of the antitumour immunity in this patient. The identification of such serum antibody-reacting proteins could facilitate the discovery of tumour neoantigens.